2021
DOI: 10.1016/j.ekir.2021.08.030
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Hesitancy in Patients on Dialysis in Italy and France

Abstract: Introduction Patients on dialysis (HDP) are a category at high risk from COVID-19 and thus a high-priority group for vaccination. COVID-19 vaccine hesitancy has been a concern since the availability of the first vaccine. The objective of this study was to determine hesitancy rates and factors associated with hesitancy towards COVID-19 vaccination in HDP. Methods HDP were surveyed with an ad hoc questionnaire in four large dialysis facilities i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 30 publications
4
26
0
Order By: Relevance
“…Regarding hesitancy of hemodialysis patients regarding SARS-CoV-2-vaccines, Garcia et al showed that one in five were reluctant to seek the COVID-19 vaccine even if the vaccine was considered safe for the general population [ 22 ]. A recent study from France and Italy showed that concerns about side effects and vaccine efficacy in dialysis patients were independent predictors for higher vaccine hesitancy [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding hesitancy of hemodialysis patients regarding SARS-CoV-2-vaccines, Garcia et al showed that one in five were reluctant to seek the COVID-19 vaccine even if the vaccine was considered safe for the general population [ 22 ]. A recent study from France and Italy showed that concerns about side effects and vaccine efficacy in dialysis patients were independent predictors for higher vaccine hesitancy [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Garcia et al found that age, gender, and educational level affect the intention of COVID-19 vaccination in an online survey conducted on MHD patients [ 14 ], our study did not confirm these findings. In another survey conducted on MHD patients, Blanchi et al stated that younger age was associated with vaccine hesitancy while hesitancy was not related to educational level and gender [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that one in three HD claimed prior personal contact with COVID-19 and one in four stated a close family member had antecedent infection, vaccine hesitancy in the high-risk dialysis population is alarming [ 10 ]. HD Patients have been reported to show high levels of vaccine hesitancy [ 11 , 12 ]. Vaccine hesitancy among these patients is not linked to their educational level, age, or gender, but rather to a lack of confidence in vaccine efficacy and safety concerns [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific trust, such as trust in vaccines, the government, the health system, or professionals, has been sufficiently explored in the context of vaccine hesitancy in general [ 24 , 25 ], and specifically for COVID-19 vaccines (trust in vaccines [ 6 , 16 , 26 – 28 ], trust in government [ 20 , 22 , 26 , 29 , 30 ], trust in healthcare system or practitioners [ 16 , 31 – 33 ]). By contrast, generalized trust, i.e., a default expectation of goodwill from other people [ 34 ] that is often viewed as an important part of social capital [ 35 ], has not been sufficiently explored in the context of vaccine hesitancy.…”
Section: Introductionmentioning
confidence: 99%